Analisis Peran Unit AMC dan Bangunan Landasan Dalam Penanganan Foreign Object Debris (FOD) di Area Apron di Bandar Udara Tunggul Wulung Cilacap - Faizah, Inani Nur; Fauziah, Syifa (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2024)
Foreign Object Debris or FOD is a foreign object that has the potential to pose a hazard to aviation safety. Supervision and maintenance of the cleanliness of the apron from the appearance of FOD is the responsibility of the Apron Movement Control (AMC) unit. This is also the responsibility of the Building and Runway unit in carrying out the function of overseeing the cleanliness of the movement area both on the land and air sides. This study aims to determine the role, constraints and anticipatory actions taken by the AMC unit and the Building and Runway unit in dealing with FOD in the apron area. This study uses qualitative research methods with data collection techniques using interviews, observation, and documentation. The type of data used is primary data in the form of the results of interviews directly with the informants, the results of observations and also documentation. There are also secondary data used such as previous research urnals, flight regulations, company documents, and other data related to research which are then processed using the triangulation method. The results of the study show that the AMC unit and the Building and Runway unit act as supervisors, controllers, and as direct follow-ups of FOD through inspection activities. The constraints experienced by the AMC unit were the lack of supporting equipment such as the absence of a follow me car, computers, CCTV, acoustic bird repellent devices, and a lack of personnel, while the constraints experienced by the Building and Runway unit were bad weather which disrupted inspection activities. As for the anticipatory actions taken, namely collaboration between units, giving directions to the flying school and routine meeting activities at the Tunggul Wulung Cilacap airport. Keywords: Apron Movement Control (AMC), Building and Runway units, Foreign Object Debris (FOD), Apron.